Assessing Public Opinion Regarding COVID-19 Vaccinations in Pakistan: Knowledge, and Perceptions of General Public: Opinion Regarding COVID-19 Vaccinations in Pakistan - Ullah, Sana; Shahid, Syed Ahsan; Hafeez, Sara; Fatima, Sara; Zia, Fatima; Ali, Muhammad (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
The COVID-19 infodemic can be counteracted by clear and consistent communication of scientific evidence and improved health literacy between the public and informants. For complete eradication of COVID-19, several vaccines are approved in various countries for public use by regulatory authorities. Assessing public perception regarding COVID-19 vaccination is an important area of research. In the current study, we aim to evaluate the opinions of individuals from multiple localities about COVID-19 and its vaccination through an online survey. Participants of the study were divided into different groups based on age, profession, demography, and income, and their opinions were calculated in percentage. In age group analysis we reported the highest willingness, 62.8 % (n=22) in age group 30-40, followed by 60 % (n=3) in age group >50, 58.6 % (n=244) in age group 20-30, 57.95 % (n=51) was in age group 15-20 and the least willingness, 33.33 % (n=4) in age group 40-50. The highest disagreement regarding vaccination of 60 % was found in age group >50, followed by 33.3 % in the age group 40-50, 14.7 % in the age group 20-30, 11.4 % in the age group 15-20 and 30-40. Similarly based on profession, maximum acceptability, 59.1 % (n=262) was reported in students, followed by a businessman (68.7 %, n=11), professional workers (3.5 %, n=20). Likewise, in demographic analysis, individuals from Khyber Pakhtunkhwa (KP) (61.3 %, n=200) were found more enthusiastic for vaccination, followed by AJK (58.33 %, n=7) and Islamabad (58.1 %, n=32). In the same way, people with income range $435 - $621/month showed the highest willingness (65.7 %, n=69) regarding vaccination, followed by income group ($621 or more $s/month). Surprisingly, individuals from the low-income group were found more interested in vaccination as compared to the higher-income group. Comparatively low interest of high-income group individuals may be due to more exposure to conspiracy theories shared on social media.